(untitled) (European Journal of Pure and Applied Mathematics, 2012)
In this paper, we introduced a quantum space generated by three noncommutativeÂ coordinates with two commutation parameters. We also give Hopf algebra structure in order toÂ construct bicovariant differential calculus over this quantum space. Morever, it is shown thatÂ noncommutative derivative operators corresponding the coordinates comprise Weyl algebra.